International law and its role in the consolidation of the Republic of Peru - Campos Maza, Gian Pierre (2024)
The objective of this paper is to identify the public international law as an instrument for the design, conduct and monitoring of actions with international impact of the nascent Peruvian republic. For this purpose, it will begin with the definition of the main categories under study such as international law, foreign policy, national objectives, among others. Next, a series of key historical events will be analyzed, such as: the break with Spain (from the declaration of independence and its legal value, to the “Treaty of Peace and Friendship” of 1879); the border delimitation process and its value for the protection of the national territory; and finally, the generation of economic alliances through the signing of commercial treaties that maintained and expanded Peru’s international projection in order to achieve recognition as an independent State in the international community. Through this examination, the role played by the application of public international law by political and military actors and decision-makers in achieving the objectives set to consolidate the new Peruvian republic will be highlighted.